2005
DOI: 10.1158/1078-0432.ccr-04-2115
|View full text |Cite
|
Sign up to set email alerts
|

Proteins and Protein Pattern Differences between Glioma Cell Lines and Glioblastoma Multiforme

Abstract: Introduction: Researchinto the pathogenesis, molecular signaling, and treatment of glioblastoma multiforme (GBM) has traditionally been conducted using cell lines derived from malignant gliomas. We compared protein expression patterns between solid primary GBMs and GBM cell lines to identify proteins whose expression may be altered in cell culture. Methods: We cultured cell lines U87, U118, U251, and A172 and used tissue-selective microdissection of eight primary GBMs to obtain pure populations of tumor cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 35 publications
6
42
0
4
Order By: Relevance
“…Our data agree with previous microarray gene expression profiling studies that have used either brain tumor cell lines or tissue from adult supratentorial gliomas [28][29][30]. We found that 15 out of the 54 differentially expressed proteins have been reported in these previous studies as potential tumor biomarkers.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our data agree with previous microarray gene expression profiling studies that have used either brain tumor cell lines or tissue from adult supratentorial gliomas [28][29][30]. We found that 15 out of the 54 differentially expressed proteins have been reported in these previous studies as potential tumor biomarkers.…”
Section: Discussionsupporting
confidence: 92%
“…We found that 15 out of the 54 differentially expressed proteins have been reported in these previous studies as potential tumor biomarkers. Among these, vimentin, peroxiredoxin-6, SOD1, annexin V, GFAP, and DRP-2 have been shown to be up-regulated in adult glioblastoma multiform (GBM) [28][29][30][31] whereas tubulin beta-2C chain, neurofilament light polypeptide, and pyruvate kinase are known to be up-regulated in meduloblastoma cell lines [29,32]. We also detected a high expression of angiogenesis-related proteins in BSG tumor compared to the normal tissue sections and these included hemoglobin subunits, which are an indication of angiogenesis, as well as periostin and mimecan precursors.…”
Section: Discussionmentioning
confidence: 99%
“…A vast number of reports deal with the biological differences between the U87MG and Dystroglycan in Human Gliomas the U251MG cell lines both in vitro and in vivo. 37,38 Xenograft implantations of U87MG and U251MG cells into the brain of nude mice display consistent and reproducible differences in tumor growth and invasion, which could also reflect the differences in α-DG glycosylation and in their proliferative response to DG overexpression. 39 In fact, the α-DG negative U87MG are more tumorigenic in nude mice brain, 40 and they grow mainly as expanding tumor mass by making spheres with little perivascular infiltration.…”
Section: A B Cmentioning
confidence: 94%
“…Следует заметить, что за последние годы протеомный сравнительный анализ в области изучения глиобластомы стал очень популярен, поэтому есть возможность для сравнения наших и уже опубликованных результатов. Необходимо отметить, что по многим белкам наши и литературные данные совпадают, например, по пируваткиназе М1/М2 [24], триозофосфатизомеразе [25], кофилину, енолазе, виментину и его разным формам [26,27]. Появление мутантных форм р53 характерно для многих опухолей, есть публикации такого рода и по глиобластомам [28].…”
Section: иммуноблотинг (вестерн-блот)unclassified